PROBIOTICS IN PERIODONTAL THERAPY - LITTY SCARIYA; NAGARATHNA D.V; MERLINE VARGHESE (International Journal of Pharma and Bio Sciences, 2015)
To partially assess the efficacy of probiotic lozenges, in the treatment of periodontal disease. Material and methods: Twenty eight subjects, of both sexes, were selected and divided into 4 groups (2 test groups and 2 control groups).The test group was instructed to consume probiotic lozenges whereas the control group did not receive any probiotic product. Clinical parameters such as plaque index, gingival index, modified sulcular bleeding index and probing pocket depth were recorded and assessed at baseline, day 15, 30, 45 and day 60. The Test group showed significant reduction in all parameters when compared to that of Control group. After stopping probiotic administration on day 30, the test group showed a significant increase in all the clinical parameters except probing pocket depth on day 45 and day 60. Conclusions: The results show that probiotic lozenges were efficacious in reducing both moderate to severe gingivitis and moderate periodontitis.